Growth of graphene on copper and nickel foils via chemical vapour deposition using ethylene. (July 2014) - Sagar, R. R.; Zhang, X.; Xiong, C.
Abstract : Graphene was grown on copper and nickel foils via chemical vapour deposition (CVD), using ethylene (C2 H4 ) as a precursor instead of methane (CH4 ). Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and high resolution transmission electron microscopy (HRTEM) results confirmed that ethylene can be used in the growth of graphene. The effect of ethylene pressure on graphene growth was also observed. This study's results show that graphene can be grown on copper and nickel foils under the same growth conditions of CVD if ethylene is used as a precursor.